RORα-activated mitophagy attenuating hypoxic-ischemic encephalopathy via suppression of microglial cGAS-STING axis - Song, Lei; Shen, Haiyan; Hong, Fei; Zhang, Weiyan; Lu, Hongyi (Frontiers in Immunology, 2025)
IntroductionHypoxic-ischemic encephalopathy (HIE) involves neuroinflammation driven by microglial activation, yet regulatory mechanisms remain poorly defined. This study investigates how Retinoic Acid Receptor-Related Orphan Receptor Alpha (RORα) modulates mitophagy to suppress mtDNA-cGAS-STING-NLRP3 signaling in aging microglia, offering therapeutic potential for HIE.MethodsA multi-omics approach combining single-cell RNA sequencing (scRNA-seq) of an HIE rat model, Weighted Gene Co-Expression Network Analysis (WGCNA), and LASSO regression identified RORα as a pivotal regulator. In vivo and in vitro HIE models with RORα overexpression were assessed via behavioral tests (morris water maze, tail suspension), reactive oxygen species (ROS) quantification, and molecular profiling (RT-qPCR, Western Blot, ELISA). Mitophagy inhibitor 3-MA was used to validate pathway dependence.ResultsMulti-omics integration revealed RORα as a hub gene linked to inflammatory and metabolic pathways. RORα activation enhanced mitophagy, reducing mtDNA leakage by 43% and cGAS-STING activity by 68%, which suppressed NLRP3 inflammasome activation (p < 0.01). This correlated with improved cognitive/motor function in HIE rats (p < 0.05) and attenuated ROS/IL-1β levels. Critically, 3-MA reversed RORα’s anti-inflammatory effects, confirming mitophagy dependence.ConclusionRORα alleviates HIE by resolving microglial neuroinflammation through mitophagic inhibition of mtDNA-cGAS-STING-NLRP3 signaling. These findings position RORα as a novel therapeutic target for HIE, bridging mitochondrial quality control and neuroimmunology.